Sanksi pembunuhan dengan sengaja dalam hukum Islam berdasarkan perbandingan mazhab dan KUHP - Afifah, Nur; Zaki, Ahmad (AL-MUQARANAH, 2025)
Marriage is a sacred bond between husband and wife that establishes a reciprocal relationship consisting of rights and obligations. This study aims to analyze the balance of rights and obligations between spouses in marriage from legal, religious, and social perspectives. Using a normative approach, the study examines how these rights and obligations are regulated in marriage law and religious values, as well as their implications for household harmony. The findings reveal that achieving a harmonious and sustainable marital relationship largely depends on a proportional understanding and balanced implementation of both parties' rights and responsibilities. This study also highlights the importance of communication and cooperation between husband and wife in fulfilling mutual responsibilities to achieve the goals of marriage.